2020
DOI: 10.1183/13993003.03276-2020
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures after COVID-19: a prospective cohort study

Abstract: Take-home message: Over 75% of patients admitted to hospital with COVID-19 have abnormal patient-reported outcome measures 3 months after symptom onset, with a third of patients reporting at least moderate impairment in major dimensions of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
255
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(272 citation statements)
references
References 14 publications
11
255
0
6
Order By: Relevance
“…At 2 months follow-up, half of the patients reported persistent fatigue, whereas dyspnea (43%) and chest pain (22%) were also highly prevalent. These findings are in line with the studies by Wong et al (2020) and Garrigues et al (2020) , both of which found nearly half of the patients complaining of breathlessness at 3 months after hospital discharge.…”
Section: Persisting Cariorespiratory Symptoms In Coronavirus Survivorsupporting
confidence: 91%
“…At 2 months follow-up, half of the patients reported persistent fatigue, whereas dyspnea (43%) and chest pain (22%) were also highly prevalent. These findings are in line with the studies by Wong et al (2020) and Garrigues et al (2020) , both of which found nearly half of the patients complaining of breathlessness at 3 months after hospital discharge.…”
Section: Persisting Cariorespiratory Symptoms In Coronavirus Survivorsupporting
confidence: 91%
“…Little is known about long-term recovery from COVID-19 disease and studies about quality of life in these patients are lacking. A study by Wong and colleagues (2020) showed that over half of previously hospitalized COVID-19 survivors had a lower quality of life (measured with EQ-5D) three months after symptom onset compared to age-matched norms of the Canadian population [7]. Our non-hospitalized population showed similar results, with 40% of the patients reporting a generic quality of life below the fifth percentile of reference values.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, the consequences of viral infections remain poorly understood and the impact of COVID-19 on quality of life in patients who have not been admitted to the hospital may be highly underestimated. To date, only a few studies, focused on hospitalized patients, demonstrated a negative impact of (suspected) COVID-19 symptoms on generic quality of life [ 6 , 7 ]. Quality of life can be assessed using generic (i.e., intended for general use, irrespective of the underlying disease) or disease-specific health status questionnaires (i.e., related to a specific condition or group).…”
Section: Introductionmentioning
confidence: 99%
“…However, these complications appear to be disturbingly common 17 and thus may further diminish work capacity. As the pandemic progresses, there is concern for lingering or even chronic symptoms beyond the respiratory system and with major quality of life implications, based on recent data 18 . Lessons drawn from previous and current pandemics and disasters must be learned, and inform future responses to these inevitable events.…”
Section: Introductionmentioning
confidence: 99%